1992
DOI: 10.1128/aem.58.1.55-65.1992
|View full text |Cite
|
Sign up to set email alerts
|

Survival, stress resistance, and alterations in protein expression in the marine vibrio sp. strain S14 during starvation for different individual nutrients

Abstract: The response of the marine Vibrio sp. strain S14 to starvation for carbon, nitrogen, or phosphorus and to simultaneous depletion of all these nutrients (multiple-nutrient starvation) was examined with respect to survival, stress resistance, quantitative and qualitative alterations in protein and RNA synthesis, and the induction of the stringent control. Of the conditions tested, carbon starvation and multiple-nutrient starvation both promoted long-term starvation resistance and a rapid induction of the stringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
2
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 55 publications
6
103
2
1
Order By: Relevance
“…Predictably, a significant overlap between carbon starvation specific proteins and those induced by various stress conditions, such as heat, nalidixic acid and cadmium exposure, was observed. In comparison, very few overlapping protein responders were observed for the nitrogen or phosphorus starvation stimulon and the proteins induced by these stress agents [4]. These findings do not correspond to what has been observed for E. coli, where a significant overlap of proteins induced in response to different starvation conditions is responsible for the resistance developed towards stresses other than starvation [24].…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Predictably, a significant overlap between carbon starvation specific proteins and those induced by various stress conditions, such as heat, nalidixic acid and cadmium exposure, was observed. In comparison, very few overlapping protein responders were observed for the nitrogen or phosphorus starvation stimulon and the proteins induced by these stress agents [4]. These findings do not correspond to what has been observed for E. coli, where a significant overlap of proteins induced in response to different starvation conditions is responsible for the resistance developed towards stresses other than starvation [24].…”
Section: Discussioncontrasting
confidence: 56%
“…It has been established that Vibrto sp. strain S14 develops resistance against other stress conditions, such as heat, UV irradiation and cadmium exposure during starvation [4]. For this organism, it was recently demonstrated that carbon rather than nitrogen or phosphorus starvation induces these responses as well as the formation of ultramicrocells [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations